2020
DOI: 10.1128/msphere.00279-20
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Cluster Transcription Factor Contributes to the Intrinsic Fluconazole Resistance of Candida auris

Abstract: The recently emerged pathogenic yeast Candida auris is a major concern for human health, because it is easily transmissible, difficult to eradicate from hospitals, and highly drug resistant. Most C. auris isolates are resistant to the widely used antifungal drug fluconazole due to mutations in the target enzyme Erg11 and high activity of efflux pumps, such as Cdr1. In the well-studied, distantly related yeast Candida albicans, overexpression of drug efflux pumps also is a major mechanism of acquired fluconazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
2
40
3
Order By: Relevance
“…Based on these reports and our findings, we therefore hypothesize that F191Δ is a new potential gain of function mutation of C. auris TAC1b , conferring azole resistance through CDR1 overexpression. Nevertheless, previous reports have shown that Tac1b might function in other, Cdr1-independent ways to decrease azole susceptibility in C. auris ( 16 , 26 ). Another genetic adaptation linked to reduced azole susceptibility in this study involves aneuploidies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Based on these reports and our findings, we therefore hypothesize that F191Δ is a new potential gain of function mutation of C. auris TAC1b , conferring azole resistance through CDR1 overexpression. Nevertheless, previous reports have shown that Tac1b might function in other, Cdr1-independent ways to decrease azole susceptibility in C. auris ( 16 , 26 ). Another genetic adaptation linked to reduced azole susceptibility in this study involves aneuploidies.…”
Section: Discussionmentioning
confidence: 89%
“…2 ). Tac1b is a transcription factor that positively regulates the expression of the ATP binding cassette (ABC) transporter Cdr1, known to be involved in azole efflux and azole resistance in C. auris ( 16 , 26 ). Gene expression analysis of strain F12 (no TAC1b mutation) and strain F13 ( TAC1b mutation obtained) confirms that the acquisition of this mutation corresponds to a significantly increased expression of CDR1 (B9J08_000164), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recently published work demonstrated primary evidence that impariment of the mitochondrial function in C. haemulonii species complex intensifies the tolerance to stress and could be related with a rearrangement in the cellular ergosterol content [ 21 ]. In this context, growing evidence from recent elegant reports has revealed that there are more complicated and unknown drug resistance mechanisms apart from the mutational modification of the azole target ERG11p in fungal pathogens [ 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, the molecular bases of intrinsic resistance in Candida spp. are unknown [ 19 , 20 ], although recent research suggests that in C. auris at least, transcriptional regulation is key [ 21 ].…”
Section: Candidiasis and The Prevalence Of Anti-fungal Resistancementioning
confidence: 99%